A practical approach and algorithm for intensifying beyond basal insulin in type 2 diabetes. Issue 9 (24th May 2018) - Goldenberg, Ronald M.; Assimakopoulos, Peter; Gilbert, Jeremy D.; Gottesman, Irving S.; Yale, Jean‐François
Abstract : Despite the availability of long‐term data demonstrating the benefits of timely and aggressive intensification of antihyperglycaemic regimens among individuals with type 2 diabetes, intensification beyond basal insulin continues to be suboptimal and a global challenge. This review summarizes the evidence surrounding the various options of advancing glucose‐lowering management beyond basal insulin and provides a practical algorithm to assist in optimizing patient care and enhancing glycaemic target achievements.